Węże-syreny św. Izydora z Sewilli. Problem atrybucji nazwy - Morta, Krzysztof (Vox Patrum, 2024)
The topic of the article is the question of the name of Arabia’s flying serpents that, according to Isidore of Seville’s account, were to be called by the name of sirens. Tales about winged serpents had had a centuries-old tradition even before Isidore, in the Greek and Latin literatures. They appeared for the first time in the 5th century BC thanks to Herodotus and his Histories II 75-76. However, not until Isidore of Seville and his Etymologiae XIV 3,7 were those serpents specifically referred to as sirens. The author of the article traces back the surviving texts by both the pagan and Christian authors. He tries to find out what the Isidore’s source of this piece of information was. As a result of his research, the author points to a mysterious mention found in St. Jerome’s Commentary on Isaiah. After its thorough analysis, based on other texts by Jerome, the author explains how the name of sirens – previously not related to the tale about Arabia’s winged serpents – has been incorporated into their description created by Isidore.